The Correlation Study between Newborn Weight and Degree of Perineal Rupture in Spontaneous Labor: The Correlation Study between Newborn Weight and Degree of Perineal Tears in Spontaneous Labor - Salsabila, Gema Alya; Diana Noor Fatmawati (Journal of Nursing Care and Biomolecular, 2025)
Introduction: Perineal rupture is a tear in the tissue between the vagina and anus that occurs spontaneously during vaginal delivery. The clinical impact of perineal rupture is quite complex, ranging from prolonged pain, impaired wound healing, dyspareunia (pain during sexual intercourse), urinary and fecal incontinence, and psychological disorders such as anxiety and postpartum trauma. Considering the high prevalence of perineal rupture, both nationally and globally, and its impact on increasing maternal morbidity and mortality due to bleeding and infection, it is important to identify preventable risk factors, one of which is birth weight. This study aims to determine the relationship between birth weight and the incidence of spontaneous perineal rupture in normal delivery at TPMB "Suharti" Lumajang. Method: This study used an analytical observational research design, with a cross-sectional approach. Result and analysis: The results of the study showed that the Spearman's rho correlation coefficient value was 0.336 with a sig level = 0.024 <0.05 so that H0 was rejected and H1 was accepted, so it can be explained that there is a significant relationship between birth weight and the incidence of spontaneous perineal rupture in normal delivery. the greater the weight of the newborn, the greater the chance of perineal rupture.